2021
DOI: 10.2478/ngoe-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Testing of Purchasing Power Parity Validity in Selected European Union Countries

Abstract: In this article, the authors carried out an empirical analysis of the validity of purchasing power parity (PPP) in Slovenia, Croatia, the Czech Republic, Slovakia and Austria. The results provide mixed support for PPP, which is typical for extransition economies. In the first phase of the empirical part of the research, the authors tested the stationarity of the real exchange rate in a logarithm, while in the second phase, the cointegration of nominal exchange rate, domestic and foreign price levels was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Papell (2006) indicated that when the dollar appreciates, the PPP is supported, and when it depreciates, the validity of the PPP is not strong. Plošinjak and Festić (2021) examined the practical fitting of the PPP theory in Slovenia, Croatia, the Czech Republic, Slovakia, and Austria, and showed mixed support.…”
Section: Previous Researchmentioning
confidence: 99%
“…Papell (2006) indicated that when the dollar appreciates, the PPP is supported, and when it depreciates, the validity of the PPP is not strong. Plošinjak and Festić (2021) examined the practical fitting of the PPP theory in Slovenia, Croatia, the Czech Republic, Slovakia, and Austria, and showed mixed support.…”
Section: Previous Researchmentioning
confidence: 99%
“…To avoid pseudo regression, the stability test of time series shall be carried out before time series analysis [20]. In this paper, Augmented Dickey-Fuller (ADF) test and Phillips-Perron (PP) test were used for the unit root test of variables.…”
Section: Existence Test Of Cointegrationmentioning
confidence: 99%